2009
DOI: 10.1002/ceat.200800474
|View full text |Cite
|
Sign up to set email alerts
|

On‐line Statistical Process Monitoring and Fault Diagnosis in Batch Baker's Yeast Fermentation

Abstract: This study involves real-time monitoring and fault diagnosis in batch baker's yeast fermentation. A specific Real Time Statistical Process Analysis and Control (RT-SPAC) program was developed to monitor instantaneous reaction conditions. The air flow rate fed to the reactor, temperature, pH, and dissolved oxygen concentration in a laboratory-size fermenter were monitored and recorded by means of on-line sensors. Under control of the RT-SPAC program, 22 batch baker's yeast fermentation operations were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…So far, ongoing research studies for all of the above three types of batch process monitoring methods have being carried out. More recent related works include those by Gunther et al, Faggian et al, Berber et al., Alvarez et al, Chen and Jiang, He and Wang, Ge and Song, and so on. To examine the advantages and disadvantages of different types of batch process monitoring methods, please refer to the recent critical evaluation and survey papers. ,, …”
Section: State-of-the-art Of Data-based Process Monitoringmentioning
confidence: 99%
“…So far, ongoing research studies for all of the above three types of batch process monitoring methods have being carried out. More recent related works include those by Gunther et al, Faggian et al, Berber et al., Alvarez et al, Chen and Jiang, He and Wang, Ge and Song, and so on. To examine the advantages and disadvantages of different types of batch process monitoring methods, please refer to the recent critical evaluation and survey papers. ,, …”
Section: State-of-the-art Of Data-based Process Monitoringmentioning
confidence: 99%
“…To locate the faulty sensitive units, a fault isolation algorithm should be carried out once a fault is detected. As a popular method, contribution plots (Bezergianni and Kalogianni, 2008; Berber et al , 2009) were commonly utilized to diagnosis fault details by evaluating the contribution of each variable. However, Westerhuis et al (2000) reported that contribution plots method suffers from fault smearing effect, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, designing an intelligent fault diagnosis method has attracted considerable attention. Various intelligent techniques have been put forward, such as expert system 1, principal component analysis (PCA) 2–5, wavelet transform 6, 7, rough set theory 8 etc. Artificial neural network (ANN) can approximate the nonlinear relations for continuous or discrete systems 9–11 and has been widely applied in fault diagnosis 12–16 in recent years.…”
Section: Introductionmentioning
confidence: 99%